MEDB-86. A re-induction regimen for children with recurrent medulloblastoma. (3rd June 2022) - O'Halloran, Katrina; Phadnis, Sheetal; Metrock, Laura; Friedman, Gregory; Davidson, Tom; Robison, Nathan; Dhall, Girish; Margol, Ashley
Abstract: Medulloblastoma is the most common malignant brain tumor of childhood. Despite multi-modal therapies, 30% of patients experience disease recurrence, which portends a poor prognosis. At initial recurrence, intensive chemotherapy may be effective prior to various consolidation therapies including high dose chemotherapy with autologous stem cell rescue or irradiation. We report outcomes for nine children treated at two institutions with the following regimen: cyclophosphamide 1500mg/m2/dose days 1, 2; irinotecan 125mg/m2/dose days 1, 8; temozolomide 150mg/m2/dose days 1-5, and oral etoposide 50mg/m2/dose days 1-7. Patients received 2-4 cycles based upon disease response and physician preference. The mean time from initial diagnosis to first recurrence was 19 months. After receiving two cycles of therapy, two patients had complete response (CR) and proceeded to consolidation. Of the remaining seven patients, five had partial response (PR) and two had stable disease (SD). Overall response rate was 78% after 2 cycles. Two patients with PR proceeded directly to consolidation with irradiation. Five patients (3 PR, 2 SD) received 2 additional cycles. After four cycles there was one CR, two with minimal residual disease, one SD and one progressive disease (PD). Four patients (44%) are alive with no evidence of disease (NED). One patient died of consolidation-related toxicity but had NED at time of death 28 months from initial recurrence. Five patients developed PD. Two patients died of disease, two are alive with disease, and one is alive with NED after PD and additional therapy. There were no treatment-related deaths. Infection was the most common complication. Five patients had febrile neutropenia and two developed sepsis. One patient required dose reduction for prolonged thrombocytopenia. Peripheral blood stem cell collection was achieved in all patients for whom it was attempted. This re-induction regimen is generally well-tolerated and effective in inducing responses for children with recurrent medulloblastoma.